Pandangan Masyarakat Awam dan Penyandang Disabilitas Mengenai Hak Kerja Penyandang Disabilitas Di Indonesia - jasmine, khayrunnisa adielya (Paradigma, 2025)
People with disabilities are often underestimated because they have both physical and mental deficiencies. Because of these shortcomings, people with disabilities often experience discrimination. This causes a decrease in the self-confidence of people with disabilities. People with disabilities are considered incompetent in doing work, which causes discrimination against the employment rights of people with disabilities. In this research, researchers conducted interviews to find out the responses of ordinary people and people with disabilities regarding the employment rights of people with disabilities who are free from discrimination. Keywords: Disabilities, Discrimination and employment.